2018
DOI: 10.1111/trf.14890
|View full text |Cite
|
Sign up to set email alerts
|

The effects of apheresis, storage time, and leukofiltration on microparticle formation in apheresis platelet products

Abstract: MP formation was affected by the apheresis procedure. RMPs, LMPs and MMPs were lower after PLT apheresis. During storage, TMPs, PMPs, RMPs, LMPs, and MMPs were found to be higher in PLT supernatants. Leukofiltration exerted no significant effect on all MPs in PLT products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…72,73 Unlike cytokines, the PMP concentrations have no significant changes after LR. 72,76 PS externalization on PMPs surface staining with annexin-V is associated with desialylation, which promotes phagocytosis by HepG2 cells. 77 Some evidence has also suggested that PMPs from PC have potential for immune function due to proteins.…”
Section: Major Bmrs Released By Plateletsmentioning
confidence: 99%
See 3 more Smart Citations
“…72,73 Unlike cytokines, the PMP concentrations have no significant changes after LR. 72,76 PS externalization on PMPs surface staining with annexin-V is associated with desialylation, which promotes phagocytosis by HepG2 cells. 77 Some evidence has also suggested that PMPs from PC have potential for immune function due to proteins.…”
Section: Major Bmrs Released By Plateletsmentioning
confidence: 99%
“…Although different types of MPs can be detected in PCs, 72,73 we primarily focus on PMPs because the concentration of other cells in PCs is minimal. PMPs, small vesicles with a diameter of 0.1-1 microns, are primarily thought to be a way for platelets to exert coagulation function through membrane or intrinsic mediators because PMPs can trigger monocytic cell aggregation and release of procoagulant tissue factor-expressing MPs.…”
Section: Major Bmrs Released By Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…These reactions may be due to the techniques used for processing, storage, and collection. 8 To improve PLT collection apheresis efficiency and quality, new instruments and improvements in cell collection technology are in constant development, aimed at reducing the duration of the procedure and its adverse effects. 9 Improvement of current plateletpheresis collection yields is a priority due to increased PLT demand, principally from hematooncology patients receiving myeloablative chemotherapy and hematology patients who require support after receiving a hematopoietic stem cell transplant.…”
Section: Introductionmentioning
confidence: 99%